Confocal depth-resolved micro-X-ray absorption spectroscopy study of chemically strengthened boroaluminosilicate glasses. Issue 29 (2nd March 2016) - Tack, Pieter; Bauters, Stephen; Mauro, John C.; Smedskjaer, Morten M.; Vekemans, Bart; Banerjee, Dipanjan; Bras, Wim; Vincze, Laszlo
Abstract : A set of chemically strengthened boroaluminosilicate glasses containing 1 mol% Fe2 O3 are here studied using depth-resolved confocal X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) spectroscopy. Abstract : It is crucial to understand the structural origins of macroscopic properties in silicate glasses for their high-tech applications. An example of such an application is chemically strengthened boroaluminosilicate glasses that are exposed to an ion exchange process during which alkali ions ( e.g. Na + ) are replaced by larger ( e.g. K + ) ions. Despite the empirically thorough understanding of this exchange process, much less is known about the fundamental physics of the process. Since Fe atoms are a suitable probe for monitoring chemical stress-induced changes in the local structure in the chemically strengthened glasses, a set of chemically strengthened boroaluminosilicate glasses containing 1 mol% Fe2 O3 are here studied using depth-resolved confocal X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) spectroscopy. Information on the Fe oxidation state, coordination number, and bond distance as a function of the sample depth and glass composition is obtained. These new insights on chemical stress-induced changes will aid in the further development and improvement of such damage-resistant glasses.